Analisis Dampak Kerajinan Rotan Terhadap Pendapatan Bagi Ibu Rumah Tangga - Sopia, Mira; Sahabudin, Sahabudin; Sanwani, Sanwani (Universitas Qamarul Huda Badaruddin, 2024)
This study aims to analyze the impact of rattan crafts on the income of housewives in Tibu Sisok Village, Janapria District. Using a descriptive qualitative approach, this study provides an in-depth description of social phenomena, particularly regarding the contribution of rattan crafts to family income. The research location is Tibu Sisok Village, Central Lombok Regency, and data collection techniques include observation, interviews, and documentation. Data sources include primary data obtained from the village head, rattan entrepreneurs, and 15 housewives, and secondary data from documentation, village profiles, and village administration reports. To ensure data validity, the researcher used source triangulation to verify the consistency of information from various sources. The results indicate that rattan crafts make a positive contribution to increasing family income. However, craftspeople face challenges such as limited raw materials, high rattan prices, lack of government support, and limited business capital. Despite this, housewives continue to maintain this activity through adaptive strategies, such as selling products online and collaborating with the rattan industry. This study recommends the need for support from the government and relevant stakeholders to strengthen the rattan craft sector as a driver of the local economy. Thus, rattan crafts can be a sustainable source of income for housewives in Tibu Sisok village.